Reviving the Essence of Jihad in the Contemporary Era: Advocating Struggle and Solidarity for Palestine Through Boycott of Pro-Israel Products - Samudra, Fawes; Zaman, Akhmad Roja Badrus; Mukti, Digdo Aji (MILRev: Metro Islamic Law Review, 2024)
The humanitarian plight of the Palestinian people is stirring global sympathy, resulting in various forms of support. Among these actions is the pro-Israel boycott movement, endorsed by Muslim scholars and intellectuals through the issuance of fatwas. Therefore, this research analyzes the conceptualization of boycotting pro-Israel products within the framework of Islamic Jihad. The literature discussing the concept of boycotts in Islam and the product movement for humanity is explored using library research methodology. The results show that contemporary Jihad includes military, political, economic, and boycott efforts. In addition, the movement is developed as a manifestation of Jihad against injustice and human rights violations according to individual capacities and circumstances. This research positions boycotts as a novel facet of Jihad in the Contemporary era, contributing to the multifaceted nature beyond traditional warfare paradigms.